PREDIKSI MATA UANG KRIPTO MENGGUNAKAN METODE ALGORITMA LINEAR REGRESSION - Matthew Oullanley Lee; Delima Sitanggang; Evta Indra (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Cryptocurrencies are advanced monetary standards planned to operate as a medium of exchange over a arrange that's free of a central specialist, such as a government or bank. Cryptocurrencies have a tendency for price changes to occur which fluctuate like conventional currencies which can cause shifts in the market. This shift can affect cryptocurrencies, especially asset owners. The goal in this research is to predict data and provide accurate results to help cryptocurrencies players. In the process, web scraping is used to retrieve data This study will visualize the data in the form of a line chart by employing the linear regression algorithm to forecast the price movement of cryptocurrencies. nonetheless, digital forms of money costs can't be isolated from outside elements, for example, the conversion standard of rupiah against unfamiliar monetary forms. There are a lot of influencing factors, like when there is more demand than there is supply. The rise in bitcoin's price from $ 19,616.81 to $ 25,995.91 is evidence of this. A rise in market capital from $ 375,367,382,007.85 to $ 504,341,343,850 also helped. A cryptocurrency's demand is proportional to its market capitalization, which indicates how dominant it will be in the stock market. The daily return is another indicator that cryptocurrency movements can be either positive or negative.